DRUG DELIVERY SYSTEMS FOR CARIES DISEASE - Loredana Liliana Hurjui; Cristina Claudia Tarniceriu; Claudia Dorus; Diana Popovici; Carmen Delianu; Raluca Jipu; Carina Balcoș; Ion Hurjui; Irina Gradinaru (Romanian Dental Association for Education, 2024)
Dental caries is a multifactorial, dynamic disease that affects dental hard tissues, being initiated by acidic products from oral biofilms. The etiology and pathophysiology of dental caries are extremely complex. It is widely accepted that changes in the local microecology and disruption of tooth re/demineralization could cause dental caries. Moreover, saliva, fluoride application, dietary sugars and preventive behaviors could also influence it. In recent decades, a combination of drug-release and controlled-release systems for the purpose of caries prevention has gradually attracted attention. These could help maintain the concentration of anti-caries agents in situ through sustained drug release. Such local application has many advantages, such as high efficacy and few systemic effects. Thus, in recent years, there has been an increasing amount of research on drug delivery systems for different stages of dental caries.